"He May Certainly Have Forgotten": Processing of Nested Epistemic Expressions. Issue 8 (14th September 2022) - Qiu, Zhuang; Ferreira, Fernanda
ABSTRACT: This article presents a series of three experiments investigating the processing of nested epistemic expressions, utterances containing two epistemic modals in one clause, such as "he certainly may have forgotten." While some linguists claim that in a nested epistemic expression one modal is semantically embedded within the scope of the other modal based on the word order, it is possible that in daily conversation the scope of nested modals may not be thoroughly processed, leading to a "good-enough" interpretation that is not sensitive to the word order of the two modals. This study used probability judgment tests to investigate people's interpretation of nested epistemic expressions, and the effect of word order was not observed. This result fails to support the scope account of the nested epistemic expressions and suggests a holistic processing mechanism in line with the good-enough processing framework.